2019
DOI: 10.4067/s0034-98872019000100024
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización de cepas clínicas y ambientales de Salmonella enterica subsp. enterica serovar Heidelberg aisladas en Chile

Abstract: Characterization of Salmonella Heidelberg strains isolated in ChileBackground: Salmonella Heidelberg (S. Heidelberg) causes gastroenteritis and sometimes bacteremia and endocarditis. In other countries, this serovar has multidrug resistance including extended-spectrum β-lactamases (ESBLs) and AmpC β-lactamases (AmpC), associated with the bla CMY-2 gene. In Chile, an outbreak by S. Heidelberg occurred in 2011, the phenotypic and genetic characteristics of Chilean strains are unknown. Aim: To determine the antim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
(58 reference statements)
1
4
0
Order By: Relevance
“…Our findings demonstrated higher phenotypic antimicrobial resistance against to AMO, AMP, COL, CFT, SMX, and TET commonly used in veterinary and human medicine routine when compared to results obtained in Brazil and Argentina (Borsoi et al, 2009;Aravena et al, 2019).…”
Section: Antimicrobial Resistance Profilesupporting
confidence: 56%
See 1 more Smart Citation
“…Our findings demonstrated higher phenotypic antimicrobial resistance against to AMO, AMP, COL, CFT, SMX, and TET commonly used in veterinary and human medicine routine when compared to results obtained in Brazil and Argentina (Borsoi et al, 2009;Aravena et al, 2019).…”
Section: Antimicrobial Resistance Profilesupporting
confidence: 56%
“…The ompC and invA genes are used to characterize the genus and the ability to invade host tissues, respectively, and the presence in all strains was expected. Together with the agfA and lpfA genes, they were previously identified in all Salmonella isolates in Brazil and Chile (Rowlands et al, 2014;Aravena et al, 2019). Both encode fimbriae-related proteins that carry essential adhesins that are associated with cell attachment to abiotic surfaces and biofilm formation for later intestinal colonization and expression of virulence, which indicates potential risk after infection (Yoo et al, 2013).…”
Section: Specific Virulence Genesmentioning
confidence: 99%
“…Gene frequency variation and genetic profile may be influencing the survival and multiplication capacity of the strains over the years, subsequently leading to an increase in the frequency of this serotype isolated from poultry sources in Southern Brazil. Aravena et al 27 analyzed SH strains isolated in Chile between 2006 and 2011 and did not observe these variations. However, Antony et al .…”
Section: Discussionmentioning
confidence: 97%
“…It is worth mentioning that the sefA gene is considered one of the target genes for detecting and serotyping S. enteritidis 22 . The acquisition and loss of specific fimbrial operons may be one of the mechanisms by which different Salmonella serotypes have been able to adapt to an increasing number of hosts 27 . Studies have shown that fimbriae have tropism by different cell types in distinct hosts.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was also identified in other livestock and foods [170][171][172] (Figure 1). The outbreaks by this serovar have been reported worldwide [173][174][175][176][177][178][179][180].…”
Section: Salmonella Heidelbergmentioning
confidence: 97%